Evaluasi Kapasitas Shelter Evakuasi Untuk Bencana Tsunami Di Kota Padang Berbasis Sistem Imformasi Geografis (SIG) - Ahmad Ade Kurniawan; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Padang city is prone to earthquakes and tsunamis because it lies at the confluence of two Indian and Asian plates . To prepare for the possibility of tsunami, some agencies have made evacuation planning . Marine and Fisheries Department and Tsunami Alert Community plan the building that can be used as an evacuation shelter in Padang . Marine and Fisheries Department has planed for as many as 152 buildings of shelters and Tsunami Alert Community has planed for as many as 93 buildings. This study evaluated the capacity of shelters that planned by Marine and Fisheries Department and Tsunami Alert Community  based on geographic information system with respect to the level of accessibility and capacity of shelters. Used to evaluate the level of accessibility of service area concept . Service area in this study means that refugees who are in the area has enough time to reach shelter before the tsunami . Used for the analysis of service area facilities Extension Network Analist contained in ArcGIS software . Assumption which used is if the speed of  the evacuation of people walk or run is 3.6 km/hour, the tsunami wave propagation time is 33 minutes and each resident requires an area of 1.65 m2 . In this study concluded that the capacity of the shelter which planned by  Marine and Fisheries Department and Tsunami Alert Community  is insufficient to accommodate prospective refugees in Padang . Based on data from the latest shelter building and the combination of the number of buildings that  planned by Marine and Fisheries Department and Tsunami Alert Community only able to accommodate 75 % of the population residing in the submergence area of the tsunami. Keywords: tsunami, shelter evacuation, geographic information system